DESCRIPTION BLOOD OF DOG XYLAZINE-KETAMINE INJECTED SUBCUTANEOUSLY - Gaol, Rosni Lumban; Sudisma, I Gusti Ngurah; Ardana, Ida Bagus Komang; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2016)
This study aims were to observe the effect of repeated injection of xylazine-ketamine subcutaneously to total erythrocytes, hamoglobin and hamatocrit levels of local dogs. Experimental animals used were 24 local dogs aged 1-2 years with a weight of 10-15 kg. The dogs were divided into three groups. First group as control, while group 2 in xylazine-ketamine combination injection with doses (2 and 10 mg / kg) and group 3 was injected xylazine-ketamine separated, with xylazine dose (2 mg / kg) and ketamine with dose (10 mg / kg) subcutaneously. Blood sampling conducted before anesthesia and post-anesthesia (recovery period) through the femoral vein. Examination of total erythrocyte used Neubauer methods, Sahlimethods used for examination of hamoglobin levels and examination of hematocrit used Microhematocrit methods. The results showed that there was no significant difference to total erythrocytes, haemoglobin and hamatocrit levels in treatment repeated injection of xylazine-ketamine combined or separated with the control group. From these results it can be concluded that repeated injections of ketamine with xilasin-xilasin dose (2 mg / kg) and ketamine (10 mg / kg BW) safety specifications to total erythrocytes, hamoglobin and hamatocrit levels and either used as an anesthetic in dogs.
Keywords: anestesi; xilasin; ketamin; eritrosit; hemoglobin; hematokrit